Penerapan pendidikan Holistik Berbasis karakter di TK Islam Bakti 24 Koto Gadang - M.SI, Rina (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2021)
Charakter education is a very important education applied to early childhood, therefore it is necessary to apply various ways to train children to have good character. Character based holistic education, has not been fully applied to the Bakti 24 Koto Gadang Islamic Kindergarten, the problem formulation in this research is how to implement character-based holistic education in the Bakti 24 Koto Gadang, the purpose of writing this thesis is to provide an overview of the character-based holistic education, This type of reseach is descriptive, which is the focus of the research, namely educators, studens and school administrator who are used as data sources. Data collection techniques used were observation, interviews and documentation. Based on the results of the research that has been carried out, it can be seen that the Bakti 24 Koto Gadang 24 has implemented character-based holistiic education by dividing the character into nine character pillars that are instilled through habituation, example, through stories, through songs and by using pillar worksheets. Keywords: Character-Based Holistic Education